2018
DOI: 10.4103/sjg.sjg_11_18
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of morbidity and mortality post emergency abdominal surgery: A national study

Abstract: Background/Aim:Emergency surgeries have increased in Saudi Arabia. This study examines these surgeries and associated complications.Patients and Methods:This was a prospective multicenter cohort study of patients undergoing emergency intraperitoneal surgery from the eight health sectors of Saudi Arabia. Patients' data were collected over 14 days.Results:In total, 283 patients were included (163 men [54.06%]). The majority of cases were open surgery (204 vs. 79). The 24 h and 30-day mortality rates for the coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the present study 6 dogs developed pulmonary complications, 2 of them pulmonary thromboembolic disease diagnosed at necropsy. Pulmonary complications were not individually analysed for associations with mortality due to low number of cases, but the development of major complications after surgery was associated with mortality (P < 0.001), as has been found in human medicine [11,13]. In human medicine it has also been demonstrated that the development of postoperative complications not only increases mortality in the immediate risk period, but also worsens long-term mortality [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study 6 dogs developed pulmonary complications, 2 of them pulmonary thromboembolic disease diagnosed at necropsy. Pulmonary complications were not individually analysed for associations with mortality due to low number of cases, but the development of major complications after surgery was associated with mortality (P < 0.001), as has been found in human medicine [11,13]. In human medicine it has also been demonstrated that the development of postoperative complications not only increases mortality in the immediate risk period, but also worsens long-term mortality [60].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency abdominal surgery carries an overall high risk of mortality, with rates of 11-23% commonly reported in human medicine [2][3][4][5][6][7]. Causes for these high mortality rates are multifactorial and different risk factors for death have been reported, including age [1][2][3][8][9][10][11], American Society of Anaesthesiology (ASA) classification [2,3,9,[11][12][13], preoperative comorbidities [8,14], diagnosis [2,13], presence of sepsis, disseminated cancer [1,2] and development of complications [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Given this broad spectrum, clinical presentation represents a challenge for the surgeon when faced with a patient with peritoneal signs that could lead to different therapeutic or diagnostic approaches that may delay the appropriate management. (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%